A History of the Use of Time Intervals after the Direct Sound in Concert Hall Design before the Reverberation Formula of Sabine Became Generally Accepted. Issue 2 (June 2013) - Postma, Bart N.J.
With the proposal of the D50 and the C80 two room acoustic parameters were introduced in which the time interval after the direct sound was taken into account. It is not widely known that comparable applications have a history which date back into the 17 th century. Already B.C. Vitruvius had noticed that echoes occurred in theatres and that these were unwanted to create good hearing conditions. During the 17 th and 18 th century a theory on echoes arose in books about general physics and sound. This theory influenced the books about architectural acoustics written during the end of the 18 th and the 19 th century and consequently concert hall design at the end of the 19 th century. Examples where the theory on echoes was used in the design are the Palais du Trocadero in Paris, the Neue Gewandhaus in Leipzig and the Salle Pleyel in Paris.